The Impulse Buying Puzzle: Unraveling Brand Image, Fashion, and Emotion: Teka-teki Pembelian Impulsif: Mengungkap Peran Citra Merek, Keterlibatan dalam Fashion, dan Nilai Hedonis dengan Emosi Positif sebagai Mediator - Arief Dwi Putranto; Mudji Astuti (Academia Open, 2022)
This study aimed to investigate the impact of Brand Image, Fashion Involvement, and Hedonic Value on Impulse Buying, with Positive Emotion as an intervening variable. A quantitative approach was employed, and 100 respondents participated through purposive sampling. The data were analyzed using PLS SEM with the assistance of Smart PLS version 3.0. The findings revealed significant effects of Brand Image, Fashion Involvement, and Hedonic Value on Impulse Buying. Additionally, Brand Image, Fashion Involvement, and Hedonic Value were found to significantly influence Positive Emotion. Positive Emotion, in turn, exerted a significant impact on Impulse Buying. Moreover, the mediating role of Positive Emotion was confirmed, as Brand Image, Fashion Involvement, and Hedonic Value were all found to significantly affect Impulse Buying through Positive Emotion. These results shed light on the complex dynamics underlying consumers' impulsive purchase behavior and emphasize the importance of emotional factors in driving such behavior. The implications of these findings provide valuable insights for marketers and retailers to develop effective strategies in capturing consumers' attention and promoting impulse buying in the global marketplace. Highlights: Brand Image, Fashion Involvement, and Hedonic Value significantly influence Impulse Buying. Positive Emotion plays a mediating role in the relationship between these factors and Impulse Buying. Understanding the complex dynamics of consumer behavior can help marketers develop effective strategies to promote impulse buying. Keywords: Impulse Buying, Brand Image, Fashion Involvement, Hedonic Value, Positive Emotion.